2008
DOI: 10.1186/1755-8166-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Small supernumerary marker chromosomes (sSMC) in humans; are there B chromosomes hidden among them

Abstract: Background: Small supernumerary marker chromosomes (sSMC) and B-chromosomes represent a heterogeneous collection of chromosomes added to the typical karyotype, and which are both small in size. They may consist of heterochromatic and/or euchromatic material. Also a predominance of maternal transmission was reported for both groups. Even though sSMC and Bchromosomes show some similarity it is still an open question if B-chromosomes are present among the heterogeneous group of sSMC. According to current theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…It supposed that the sSMC might represent a multifold amplification of a very small region of the genome, analogously to that have been seen in homologously staining regions (HSRs) and double minutes (DMs) described in some types of tumour cells [7][8][9][10]. Liehr T et al have reported a patient from whom the similar results were obtained [11].They suggested that a minority of sSMC show similarities to B-chromosomes.…”
Section: Discussionsupporting
confidence: 64%
“…It supposed that the sSMC might represent a multifold amplification of a very small region of the genome, analogously to that have been seen in homologously staining regions (HSRs) and double minutes (DMs) described in some types of tumour cells [7][8][9][10]. Liehr T et al have reported a patient from whom the similar results were obtained [11].They suggested that a minority of sSMC show similarities to B-chromosomes.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, the presence of an sSMC does not cause reproductive problems in all carriers. However, as sSMC and B chromosomes show some similarities, it has been suggested that it may be an evolutionary mechanism which can be observed in infertile males, i.e., genetic drift by which nature tries to get rid of the otherwise harmless sSMC via the male germline [Liehr et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…In general, sSMC can be derived from each of the 24 human chromosomes, although sSMC with no chromosomal origin determined have also been reported (Mackie Ogilvie et al 2001;Liehr et al 2008). Also, UPD can in principal appear for all human chromosomes (Liehr et al 2004;Rodríguez-Santiago et al 2010;Liehr 2011aLiehr , 2011b.…”
Section: Chromosomal Originmentioning
confidence: 99%